THE DEVELOPMENT OF CLINICAL THINKING IN MEDICAL STUDENTS DURING THE PROCESS OF STUDING THE THEORETICAL SUBJECTS - Гуранич, Т. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Professional thinking of medical personnel, first of all doctor’s, is distinguished by its peculiarity and individuality. It is formed under the influence of professional knowledge, cleverness, experience and is called clinical. The continuous development, training and improvement of clinical thinking is very important, that is started from the first years of education of students in higher medical institutions. It is necessary to create in future medics the conditions for development observation, medical intuition, ability to notice the smallest details during the process of their education. It should start to develop the clinical thinking from the first years of study, separately, during the studying of basic theoretical subjects. Only on the base of deep theoretical knowledge the doctor can farsightedly predict the clinical situation. That’s why, the ability of clinical thinking must be essential feature of professional specialist.